The future of grand challenges research: Retiring a hopeful concept and endorsing research principles - Christian Seelos; Johanna Mair; Charlotte Traeger (International Journal of Management Reviews, 2022)
Editorial notes in leading management journals have urged scholars to address Grand Challenges (GC) as an opportunity for producing knowledge that matters for society. This review explores whether current conceptualizations of GC support a productive path for management and organizational scholarship by guiding empirical inquiry, facilitating cumulative theory development, and informing practice. We systematically examine scholarly articles, calls for papers, and editorial notes published in management journals for consistency in how researchers use and define the concept of GC and the scope of associated phenomena and attributes. We find three prominent conceptual architectures in use: discursive, family resemblance, and phenomenon driven. The variety and incoherence of current uses of the GC concept and the lack of efforts to improve its analytical competence lead us to suggest its retirement. Instead, we propose building on the enthusiasm around GC research and using GC as a term to define research principles that collectively help align research efforts and improve theoretical development and practice. The principles we propose capture a genuine origin story for management research on GC.
Keywords: 650